Management of outbound tourism at siti sundari bike park as recreational and tourism sports in Lumajang Regency - Tri Vinna Fitriyana; Soni Sulistyarto; Muhammad Dzul Fikri; Hijrin Fithroni (PHEDHERAL, 2023)
This study aims to determine the management of Outbound Tourism Siti Sundari Bike Park. This type of research is a survey with a qualitative descriptive approach. The sampling technique used was snowball sampling with the research subject being the head of the Outbound tour, the tour foreman, the head of the Raja Giri Non-Governmental Organization (NGO), Outbound trainers, and culinary stall sellers. Data collection techniques using observation, interviews and documentation. Data analysis uses (data reduction, data presentation) to draw conclusions. Based on the results of the study it was found that 1) Planning (Planning) had not been fully realized properly which resulted in unmaintained Outbound facilities and tourist facilities such as homestays, toilets and culinary stalls that had been damaged. 2) Organizing is carried out by dividing the work for each employee according to their expertise and all coordinators for each vehicle carry out their duties properly according to SOP, have a good attitude and responsibility in their work. 3) Actuating (direction) has been carried out in accordance with the existing briefing procedures by the head of the Outbound tour. Each briefing is carried out in coordination meetings, both in coordination with staff and with field coordinators. 4) Controlling has been running according to its function carried out on two things, namely controlling employees and controlling the implementation of Outbound activities directly. The conclusion of this research is that Outbound management has been carried out in accordance with the management function.